An archaebacterial homologue of the essential eubacterial cell division protein FtsZ. - Baumann, P (1996)
Life falls into three fundamental domains--Archaea, Bacteria, and Eucarya (formerly archaebacteria, eubacteria, and eukaryotes,. respectively). Though Archaea lack nuclei and share many morphological features with Bacteria, molecular analyses, principally of the transcription and translation machineries, have suggested that Archaea are more related to Eucarya than to Bacteria. Currently, little is known about the archaeal cell division apparatus. In Bacteria, a crucial component of the cell division machinery is FtsZ, a GTPase that localizes to a ring at the site of septation. Interestingly, FtsZ is distantly related in sequence to eukaryotic tubulins, which also interact with GTP and are components of the eukaryotic cell cytoskeleton. By screening for the ability to bind radiolabeled nucleotides, we have identified a protein of the hyperthermophilic archaeon Pyrococcus woesei that interacts tightly and specifically with GTP. Furthermore, through screening an expression library of P. woesei genomic DNA, we have cloned the gene encoding this protein. Sequence comparisons reveal that the P. woesei GTP-binding protein is strikingly related in sequence to eubacterial FtsZ and is marginally more similar to eukaryotic tubulins than are bacterial FtsZ proteins. Phylogenetic analyses reinforce the notion that there is an evolutionary linkage between FtsZ and tubulins. These findings suggest that the archaeal cell division apparatus may be fundamentally similar to that of Bacteria and lead us to consider the evolutionary relationships between Archaea, Bacteria, and Eucarya.